YouTube as a Source of Patient Information for Knee Osteoarthritis Exercises - Fatih Bağcıer; Elem Yorulmaz; Mustafa Hüseyin Temel (Galenos Yayinevi, 2021)
Objective:Exercise therapy is the most important approach in knee osteoarthritis (OA). This study aimed to analyze the quality and reliability of exercises related to knee OA treatment found on the YouTube platform and contribute to this field, which have popularity in the literature.Materials and Methods:The keywords "knee osteoarthritis exercises," "knee osteoarthritis rehabilitation," "knee osteoarthritis physiotherapy," and "knee osteoarthritis physical therapy" were searched on YouTube on June 3, 2020. According to the global quality scale, the educational quality of YouTube videos was evaluated as high quality, intermediate, and low quality. The reliability of the videos was evaluated with the modified DISCERN score. Video source, upload date, and the number of views, likes, and dislikes parameters were documented. These parameters were compared between the groups.Results:Of the 130 evaluated videos, 46.2% (n=60) were of high quality, wherein 38.3% (n=23) were uploaded by non-physician health personnel. No low-quality video was uploaded by physicians. High-quality videos were uploaded more recently than intermediate and low-quality videos (p<0.05). Additionally, the video duration in the high-quality video group was significantly higher than the medium and low-quality videos (p<0.05). The modified DISCERN score was found to be significantly higher in the high-quality video group. The modified DISCERN score of intermediate quality videos was significantly higher than the group of low-quality videos (p<0.05)Conclusion:YouTube can be considered as a source with quality and reliable content in exercise videos related to knee OA treatment. Physicians who have the highest potential to produce quality videos should be encouraged to produce more videos.